Genome-Wide Identification of Jatropha curcas Aquaporin Genes and the Comparative Analysis Provides Insights into the Gene Family Expansion and Evolution in Hevea brasiliensis - Zou, Zhi; Yang, Lifu; Gong, Jun; Mo, Yeyong; Wang, Jikun; Cao, Jianhua; An, Feng; Xie, Guishui (Frontiers in Plant Science, 2016)
Aquaporins (AQPs) are channel-forming integral membrane proteins that transport water and other small solutes across biological membranes. Despite the vital role of AQPs, to date, little is known in physic nut (Jatropha curcas L., Euphorbiaceae), an important non-edible oilseed crop with great potential for the production of biodiesel. In this study, 32 AQP genes were identified from the physic nut genome and the family number is relatively small in comparison to 51 in another Euphorbiaceae plant, rubber tree (Hevea brasiliensis Muell. Arg.). Based on the phylogenetic analysis, the JcAQPs were assigned to five subfamilies, i.e., 9 plasma membrane intrinsic proteins (PIPs), 9 tonoplast intrinsic proteins (TIPs), 8 NOD26-like intrinsic proteins (NIPs), 2 X intrinsic proteins (XIPs) and 4 small basic intrinsic proteins (SIPs). Like rubber tree and other plant species, functional prediction based on the aromatic/arginine selectivity filter, Froger’s positions and specificity-determining positions showed a remarkable difference in substrate specificity among subfamilies of JcAQPs. Genome-wide comparative analysis revealed the specific expansion of PIP and TIP subfamilies in rubber tree and the specific gene loss of the XIP subfamily in physic nut. Furthermore, by analyzing deep transcriptome sequencing data, the expression evolution especially the expression divergence of duplicated HbAQP genes was also investigated and discussed. Results obtained from this study not only provide valuable information for future functional analysis and utilization of Jc/HbAQP genes, but also provide a useful reference to survey the gene family expansion and evolution in Euphorbiaceae plants and other plant species.